Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Skincare Kahf dengan Kepercayaan Intervening - Dimas Kamajaya Pasaribu; Syaefulloh Syaefulloh (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the effect of product quality and brand image on the purchase decisions of Kahf skincare products, with consumer trust as an intervening variable among students of the Faculty of Economics and Business at Universitas Islam Riau. This research employs a quantitative approach using a survey method through questionnaires distributed to active students who have used Kahf products. The research variables include product quality (X1), brand image (X2), consumer trust (Y), and purchase decision (Z). Data analysis was conducted using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4 software. The results indicate that product quality and brand image have a positive and significant effect on consumer trust and purchase decisions. Furthermore, consumer trust is found to mediate the relationship between product quality and brand image and purchase decisions. These findings are expected to contribute to the development of marketing knowledge, particularly in the context of young Muslim consumer behavior, and to serve as a consideration for companies in designing effective marketing strategies for men’s skincare products